Effect of Mulch Application and Different dates of Transplanting under Low Tunnel on Growth, Yield and Economics of Chilli (Capsicum annuum L.) - Tejpreet Kaur1, Kulbir Singh, S. K. Jindal, S. S. Walia and Dilpreet Talwar (Indian Journal of Extension Education, 2018)
The present investigation was conducted for two consecutive years i.e. 2016-17 and 2017-18 at Departmentof Vegetable Science, Punjab Agricultural University, Ludhianato study the effect of mulching and date oftransplanting under low tunnel on plant microclimate and growth. Plant height and number of brancheswere observed maximum in treatments that were transplanted on 15th December under polythene mulchblack, however, plots that were mulched with black polythene and transplanted on 15th February took leastnumber of days to reach 50% flowering. Yield parameters (number of fruits plant-1, fruit yield g plant-1 andtotal fruit yield q ha-1) were maximum with application of polythene mulch black and transplanted on 30thNovember and was statistically at par with 15th December transplanting which might be due to longer cropduration. Early crop and higher yields results in obtaining more net returns, thus, economically provingfeasible option for farmers.Therefore, transplanting on 30th November and 15th December under blackpolythene mulch could be beneficial for obtaining early yield and higher returns.